PEMBUATAN KOMPOS DAN ARANG KOMPOS DARI SERASAH DAN KULIT KAYU TUSAM - Sri Komarayati; Gusmailina Gusmailina; Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
this investigation deals with manufacturing of compost and charcoal compost. The raw materials in this manufacture were foliage litters and bark of tusam (Pinus mcrkusii Jungh et de Vries) trees growing in West Java. Particular bio-activators, called as Orgadec and EM;. were used to stimulate the decomposition of those materials. This investigation lasts for about three months. The results revealed that the quality of several of the resulting charcoal composts comply with the related standards, with respect to among others : P = 1.12 - 1.24 percent; K = 1.47-1. 62 percent; Mg= 0.67-1.05 percent; moisture content 55.81-56.21 percent: pH 6.8-7.2; and C/N ratio 18,89-20./0. When compared to other compost, the charcoal compost revealed better qualities, since charcoal was added to it lo improve the properties of soil, i.e. increasing the pH and storing more water.